2016
DOI: 10.1016/j.biopsych.2015.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Stress, and Fear Response in Mice With Reduced Endocannabinoid Levels

Abstract: Our findings demonstrate that the deletion of Dagla adversely affects the emotional state of animals and results in enhanced anxiety, stress, and fear responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
121
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 43 publications
14
121
1
2
Order By: Relevance
“…In support of this premise, the enzymes that produce several classes of lipid transmitters, including lysophospholipids (6), eicosanoids (7), and endocannabinoids (8,9), are highly expressed in the nervous system and play important roles in brain development, synaptic plasticity, and the modulation of complex behaviors. For example, the diacylglycerol (DAG) lipase enzymes DAGLα and DAGLβ (10) produce the endocannabinoid 2-arachidonoylglycerol (2-AG) (11,12), and the constitutive genetic disruption of DAGLα lowers brain 2-AG and arachidonic acid (AA) content (13,14), resulting in impaired synaptic plasticity (13,14), hypophagia (15), enhanced anxiety and fear responses (16,17), and propensity for spontaneous seizures (15).…”
mentioning
confidence: 99%
“…In support of this premise, the enzymes that produce several classes of lipid transmitters, including lysophospholipids (6), eicosanoids (7), and endocannabinoids (8,9), are highly expressed in the nervous system and play important roles in brain development, synaptic plasticity, and the modulation of complex behaviors. For example, the diacylglycerol (DAG) lipase enzymes DAGLα and DAGLβ (10) produce the endocannabinoid 2-arachidonoylglycerol (2-AG) (11,12), and the constitutive genetic disruption of DAGLα lowers brain 2-AG and arachidonic acid (AA) content (13,14), resulting in impaired synaptic plasticity (13,14), hypophagia (15), enhanced anxiety and fear responses (16,17), and propensity for spontaneous seizures (15).…”
mentioning
confidence: 99%
“…However, whether 2-AG deficiency states could contribute to the pathologic expression of anxiety and depressive behaviors is unknown. In the past 6 months, two studies, by Shonesy et al (Table 1), although Jenniches et al (4) additionally found that conditioned fear extinction was impaired in Dagla 2/2 mice ( Table 1). The remarkable concordance of the findings from different mouse lines and different laboratories provides strong support for the hypothesis that 2-AG signaling plays a key role in the regulation of emotional behavior and stress responsivity.…”
mentioning
confidence: 91%
“…Second, Jenniches et al (4) generated Dagla 2/2 mice from homozygote breeders, yet showed that maternal behavior was impaired in Dagla 2/2 female mice, which could potentially confound interpretation of behavioral differences between genotypes in adulthood. Lastly, Jenniches et al (4) reported reductions in the levels of anandamide in addition to 2-AG in several brain regions, whereas Shonesy et al (4) did not observe changes in forebrain anandamide levels. Although the reasons for the differences are unknown at the present time, resolution of these discrepancies should be a high priority for future studies.…”
mentioning
confidence: 91%
See 2 more Smart Citations